DISPARITAS PELINDUNGAN HUKUM DALAM PENENTUAN STATUS HUBUNGAN KERJA: STUDI KOMPARATIF PUTUSAN PENGADILAN INDONESIA DAN FILIPINA: Disparity Of Legal Protection In Determining Employment Status: A Comparative Study Of Indonesian And Philippine Court Decisions - Farhan Nugraha; Adiasih, Ning (Faculty of Law, Universitas Trisakti, 2026)
Legal certainty regarding employment status serves as a fundamental element in protecting workers' rights. The problem of this study aims to analyze the disparity in legal protection concerning the determination of employment status between Indonesia and the Philippines through a comparative study of two contradictory court decisions. This research employs a normative juridical method with case and comparative approaches. The findings reveal a significant legal paradox. In Indonesia, Decision Number 56/Pdt.Sus-PHI/2024/PN Smg affirms a rigid legal formalism that causes atypical workers (golf caddies) to lose their substantive rights despite decades of service, due to the administrative non-fulfillment of the wage element. Conversely, in the Philippines, the ruling in Paolo Landayan Aragones v. Alltech Biotechnology Corporation applies the doctrine of perfection of contract, providing progressive legal protection to prospective employees from the moment of job offer acceptance, even before physical work commences. This study concludes that a reconstruction of Indonesian labor law is necessary to shift from a formal-procedural approach to one that is more responsive to material facts of economic subordination to achieve social justice